The Utility of Screening for Coccidioidomycosis in Recipients of Inhibitors of Tumor Necrosis Factor α. (2nd August 2018) - Choi, Kristal; Deval, Neha; Vyas, Anuj; Moran, Conor; Cha, Stephen S; Mertz, Lester E; Pasha, Shabana F; Yiannias, James A; Blair, Janis E
Abstract: Background: Tumor necrosis factor α inhibitors (TNFi) are commonly used to treat immune-mediated disorders, but they are associated with an increased risk of mycobacterial and fungal infections. We compared the outcomes of TNFi recipients screened for asymptomatic coccidioidomycosis with those of unscreened patients to compare the development of symptomatic coccidioidomycosis and to describe its outcomes for patients with abnormal coccidioidal screenings. Methods: We searched electronic health records from 4 September 2010 through 26 September 2016 for all patients receiving a TNFi for dermatologic, rheumatologic, or gastroenterologic diagnoses, then categorized patients by whether or not they had undergone coccidioidal serologic testing for screening or diagnostic purposes. Results: A total of 2793 patients had a TNFi prescribed. Of those, 1951 met the inclusion criteria: 1025/1951 (52.5%) never had coccidioidal screening; 925/1951 (47.4%) had serologic screening either before beginning TNFi therapy or annually, or both after beginning a TNFi. Symptomatic coccidioidomycosis developed in 35/1025 (3.4%) unscreened patients. Of those screened, 861/925 (93.1%) had negative serologic tests, of which 11/861 (1.3%) subsequently developed symptomatic coccidioidomycosis; 36/925 (3.9%) had coccidioidomycosis at screening (7, probable infection; 11, possible infection; 18, asymptomatic seropositive result); and 17 had only positive findings for immunoglobulin M antibodies and did not meet the definition for coccidioidomycosis. The unscreened cohort was more likely to have symptomatic coccidioidomycosis than the screened cohort (35/1025 vs 11/861, P < .01). Conclusions: Screening for asymptomatic coccidioidomycosis within a Coccidioides -endemic area allowed for identifying and managing asymptomatic coccidioidomycosis before patients began TNFi therapy. Less symptomatic infection developed in the screened than the unscreened cohort. Abstract : Among recipients (or potential recipients) of tumor necrosis factor α inhibitors who resided in a Coccidioides -endemic area, a patient cohort screened for coccidioidomycosis had less subsequent symptomatic coccidioidomycosis than an unscreened cohort.